PENGEMBANGAN MEDIA PEMBELAJARAN DAILY ACTIVITY BERBASIS UNITY3D PADA PEMBELAJARAN KOSAKATA KATA KERJA DAN KATA KERJA BAHASA JEPANG TINGKAT DASAR DI SMAN 1 KREMBUNG TAHUN AJARAN 2018-2019 - KARTIKASARI, DIA (HIKARI, 2020)
AbstractThis study discusses the potential and problem of potential outcomes and problems caused to class XI students of SMAN 1 Krembung language where 86% said have difficulties in learning Japanese especialy verbs. 86% of studensts need some media to learn Japanese. 100% of students stated that they often use smartphones. Thru that case the researcher develop a media called daily activity for learning Japanese verb vocabulary. This study describe the process of developing daily activity learning media activities, the feasbility of daily activities media, and students? responses to learning media on daily activities. This research is a research development using Sugiyono?s research model. The data source in this study is the book minna no nihon go unit 6 dan sakura book 3 chapter 23-30. The subject in this study were students of class XI in SMAN 1 Krembung leaguage and students of class XI in SMAN 1 Porong. The data used is the process of developing daily learning media activities, result media validation, result validatio material, result of pre-test and post-test average values, and students responses. The proses of developing a media daily activities are 10 thing, namely potential and problems, data collection, product design, validation design, design revision, product trials, product revisionis, trial use, product revision and mass production. In this research, it reached the 9th stage, namely the revision of the product was nit approved at the 10th stage because of the time, energy and cost. Media validation is carried out by media experts and material experts. The percentage of result of media validation from media experts at 88.9% is included in the excellent category. Furthermore, media validation from material experts was 80.8% with an excellent category from validator 1 and 94.6% with an excellent category from validator 2. The average pre-test score was 69 and the post-test was 91. Based on calculations the average value of the pre-test and the post-test, student learning outcomes improved after using the media to learn daily activities by 87.6% with a very strong category. Then it can be dismantled as daily learning media and not used as a learning medium for Japanese verb vocabulaty. Keyword : Smartphone, this research, learning media daily activity ?? ???????????Daily Activity ??????? ???????????????????????????????????Krembung ???XI Bahasa ????????????????????86?????????????????????86????????????????????????????100???????????????????????????????????????????????????Unity 3s???????Daily Activity?????????????????????????????????? 1. Unity 3s????????????????????????????????Daily Activity??????????????????????? 2. Unity 3s????????????????????????????????Daily Activity???????????????????? 3. Unity 3s????????????????????????????????Daily Activity????????????????????????? ??????????????????Sugiyono???????????????????6???????22?30??????Krembung ???XI Bahasa ?????????Porong ???XI Bahasa ???????????????????????????????????????????????????????????????????Daily Activity??????????????????????????????????????????????????????????9?????????????????????????????9???????????????????????????????????????? ???????????????????????????????????????????????????????????88.9????????????????????????2?????????????????????80.8% ????94.6% ?????????????????????????????????????69????????????????91??????????????????????????????????Daily Activity?????????????????????????Daily Activity???????????????????????????????87.6????????????????????????????????????????Daily Activity???????????????????????